Seleção de espécies e procedências de Pinus para região de Assis, Estado de São Paulo - De Souza, Francine Beatriz [UNESP]; Freitas, Miguel Luiz Menezes; De Moraes, Mario Luiz Teixeira [UNESP]; Boas, Osmar Vilas; Sebbenn, Alexandre Magno (Instituto de Pesquisa e Estudos Florestais (IPEF), 2016)
The objective of the study was the selection of Pinus species and provenances for the region of Assis, state of São Paulo. The species and provenance test was established at the Assis State Forest, using the randomized blocks design with treatments represented by species (Pinus oocarpa, P. maximinoi and P. tecunumanii) and provenances of the species, four blocks and square plots with 49 plants (7 × 7), at a spacing of 3 × 2.5 m. At 21 years after planting the traits were measured: diameter at breast height (DAP), total height (ALT), individual real volume (VOL) and the survival rate (SOBRE). Significant differences were observed between species and provenances of different species (p< 0.01) for SOBRE, indicating the possibility of selection among species and provenances. The genetic divergence between species varied between growth traits from zero to 0.141, and was 0.683 for SOBRE, indicating that most of the genetic variation is distributed within species for growth traits and between species for SOBRE. Genetic and phenotypic significant and positive correlations were observed between the DAP and VOL (minimum 0.926; p< 0.01) indicating that selection for the DAP will result in an increase in the VOL. The results indicate that there are genetic variations among Pinus species and provenances of different species for SOBRE and P. oocarpa is most suitable for commercial reforestation in environmental conditions of Assis.
Selection of Pinus species and provenances for Assis region, State of São Paulo
Keywords: Genetic variation; Quantitative traits; Tree breeding